Killer's kiss - Stine, R. L. (Stine, R. L. Fear Street., 2005)
Delia and Karina have always competed against each other in everything from the top grades to the cutest guy. But suddenly they both vie for Vincent. Karina is out to get Vincent no matter what and if she can't have him, no one else can including Delia.